A case of pediatric Ramsay Hunt syndrome: diagnostic vigilance and prompt management - Christina, Jessica; Sucipta, Anak Agung Made; Suryawan, I Wayan Bikin (Indonesian Pediatric Society, 2025)
Ramsay Hunt syndrome (RHS) is a neurological disorder due to geniculate ganglion infection caused by reactivated latent varicella zoster virus (VZV). RHS is rare condition in children, with an incidence estimated at 2.7/100,000 children per year. Studies on pediatric RHS have been very limited and opinions differ on the best option for treatment.